Inactivation of Toxoplasma gondii on blueberries using low dose irradiation without affecting quality. (March 2017) - Lacombe, Alison; Breard, Anna; Hwang, Cheng-An; Hill, Dolores; Fan, Xuetong; Huang, Lihan; Yoo, Byong Kwon; Niemira, Brendan A.; Gurtler, Joshua B.; Wu, Vivian C.H.
Abstract: Toxoplasma gondii is a common protozoan parasite, whose environmentally-resistant stage, the oocyst, can contaminate irrigation water and fresh edible produce. Current washing steps in produce processing may not be effective for eliminating T . gondii from at-risk varieties of produce. The objective of this study was to evaluate low-dose irradiation as a means to inactivate T . gondii oocysts on blueberries. Blueberries (10 g) inoculated with T . gondii (5 log oocysts/g) were exposed to an absorbed dose of 0 (control), 0.2, 0.4 or 0.6 kGy gamma radiation at 4° C. After treatment, oocysts were recovered from berries by washing, and excysted sporozoites were enumerated using a plaque assay. Vero cells were maintained as monolayers in a 6-well microplate, exposed to sporozoites recovered from berries, and incubated for 7 days to determine plaque-forming units (PFU). Immediately after treatment, blueberries without inoculated T . gondii were analyzed for compression firmness, surface color, and total anthocyanins. The results from this experiment demonstrate that the viability of T . gondii oocysts was significantly reduced after an irradiation treatment of 0.2 kGy. All treatments produced reductions of 4 log PFU/g beyond the detection limit of 1 log PFU/g. Quality analysis showed that there was no significant change in compression firmness, anthocyanins, or color in berries after the irradiation treatment. Results of this study indicated that low-dose irradiation is a potential intervention measure for controlling T . gondii contamination on blueberries without affecting product quality. Highlights: Toxoplasma contamination is a concern for fresh produce. Irradiation treatments at 0.2 kGy effectively inactivate T . gondii oocysts on blueberries. Minimal impact on texture, color, or anthocyanin content of treated produce.